A new scenario-based approach to damage detection using operational modal parameter estimates. (15th September 2017) - Hansen, J.B.; Brincker, R.; López-Aenlle, M.; Overgaard, C.F.; Kloborg, K.
Highlights: A scenario-based damage assessment technique is proposed. Within the scenario frame work the technique is able to locate and quantify structural alterations. The article features an investigation of the available modal information for successful application. The technique is demonstrate on experimental test cases based on 1200 modal tests. Abstract: In this paper a vibration-based damage localization and quantification method, based on natural frequencies and mode shapes, is presented. The proposed technique is inspired by a damage assessment methodology based solely on the sensitivity of mass-normalized experimental determined mode shapes. The present method differs by being based on modal data extracted by means of Operational Modal Analysis (OMA) combined with a reasonable Finite Element (FE) representation of the test structure and implemented in a scenario-based framework. Besides a review of the basic methodology this paper addresses fundamental theoretical as well as practical considerations which are crucial to the applicability of a given vibration-based damage assessment configuration. Lastly, the technique is demonstrated on an experimental test case using automated OMA. Both the numerical study as well as the experimental test case presented in this paper are restricted to perturbations concerning mass change.